PEMBERANTASAN TINDAK PIDANA KORUPSI Hukum Non Sistemik dan Hukum Profetik - Gufroni Gufroni (PROGRESIF: Jurnal Hukum, 2019)
This article examines the empirical facts about the failure of the state (government) to eradicate this already acute corruption. Although there are laws that regulate it and there is already a special commission to eradicate corruption, namely the KPK, many still fail. The main cause is that our law still adheres to the all-mechanical-formal-legalistic system built by legal positivism. So on that basis there needs to be a new formulation as an alternative effort to make Indonesia free from corrupt practices. This study uses two theoretical approaches, namely non-systemic law / chaos theory and prophetic law. According to chaos theory, Charles Sampford in his book entitled The Disorder of Law Critical of Legal Legal Theory is not seen as a system-mechanical building, but also as liquid reality. Chaos theory states, legal theory that must be understood as a system-mechanical chaos theory (according to the view of legal positivism) is clearly a mistake, that is a mistake from the beginning in photographing legal reality. The Prophetic law is one approach in understanding the contents of the verses of the Koran. This approach focuses more on empirical, historical and temporal aspects. In the prophetic paradigm, Kuntowijoyo understands that knowing God and learning revelation are important elements in explaining reality. He took this view from a Japanese scholar, Toshihiko Izutsu, who put up his work on the Semantic Al-Qur'an Field, in the title of God and Man in the Koran: Semantics of the Koranic Weltanchauung. Of the two new offers in the effort to eradicate corruption, it was found empirical facts that there is something wrong in understanding corruption itself so that it still remains a disease that threatens the moral of a nation. The key must be courage not to be confined in the shackles of the mechanically-formal-legalistic positivism of law.